2013
DOI: 10.1021/la403397d
|View full text |Cite
|
Sign up to set email alerts
|

Dispersions of Attractive Semiflexible Fiberlike Colloidal Particles from Bacterial Cellulose Microfibrils

Abstract: We prepared dispersions from bacterial cellulose microfibrils (CMF) of a commercial Nata de Coco source. We used an ultra-high-energy mechanical deagglomeration process that is able to disperse the CMFs from the pellicle in which they are organized in an irregular network. Because of the strong attractions between the CMFs, the dispersion remained highly heterogeneous, consisting of fiber bundles, flocs, and voids spanning tens to hundreds of micrometers depending on concentration. The size of these flocs incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…In recent study Cruys-Bagger et al proposed that cellulose concentration dependent reduction in the surface area was responsible for lower association rate constants between cellulose and Tr Cel7A observed at higher cellulose concentrations [28]. Consistent with the binding data reported here a recent scanning electron microscopy study by Kuijk et al demonstrated the BC concentration dependent formation of large flocks and aggregates in BC suspensions [56]. Association of BC microfibrils should lead to the exclusion of some of the surface area for the binding of cellulases.…”
Section: Resultssupporting
confidence: 86%
“…In recent study Cruys-Bagger et al proposed that cellulose concentration dependent reduction in the surface area was responsible for lower association rate constants between cellulose and Tr Cel7A observed at higher cellulose concentrations [28]. Consistent with the binding data reported here a recent scanning electron microscopy study by Kuijk et al demonstrated the BC concentration dependent formation of large flocks and aggregates in BC suspensions [56]. Association of BC microfibrils should lead to the exclusion of some of the surface area for the binding of cellulases.…”
Section: Resultssupporting
confidence: 86%
“…The microfibrils of BC are ribbon‐shaped due to the interfibril hydrogen bonding and van der Waals attraction. These microfibrils have the tendency to agglomerate into a space‐filling network and exhibit gel‐like properties (Kuijk et al., ). The length of the microfibrils is of the order of micrometer, whereas their width is of the order of nanometer (Geyer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, BC microfibril dispersions prepared from the well‐known dessert in Philippines, named Nata de Coco (Phisalaphong & Chiaoprakobkij, ), through high energy deagglomeration has been characterized by Kuijk et al. () and further modified with addition of a charged polymer by Veen et al. (Veen, Kuijk, Versluis, Husken, & Velikov, ; Veen, Versluis, Kuijk, & Velikov, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the flow profile of a hair gel containing carbopol (in gray) is linear, implying the absence of non-locality. in the 1-100 μm range with a medium floc size of 15 μm (Kuijk et al, 2013). The length scale of these heterogeneities is comparable to ξ, implying that they might persist in BCMF dispersions even after addition of CMC.…”
Section: Resultsmentioning
confidence: 96%
“…Cellulose MFs have a strong tendency to aggregate due to Van der Waals and hydrogen bond driven interactions (Cousins, 1995) BCMFs have only a low ζ-potential (-7.5 mV), which is too low to stabilize them in aqueous suspensions, leading to their flocculation and sedimentation (Kuijk et al, 2013;Veen, Kuijk, Versluis, Husken, & Velikov, 2014). Optical setups were used to measure floc sizes in MFPC dispersions under shear (Karppinen et al, 2012;Saarikoski, Saarinen, Salmela, & Seppälä, 2012;.…”
Section: Introductionmentioning
confidence: 99%